Tryptophan intake, not always the more the better - Hu, Dongmei; Liu, Junyi; Yu, Wanlin; Li, Chuan; Huang, Lihua; Mao, Wei; Lu, Zhaoyu (Frontiers in Nutrition, 2023)
Abstract Objectives: To investigate the effects of excessive tryptophan intake on the body and the effects of tryptophan metabolism-related aryl hydrocarbon receptor (AhR) pathway in healthy rats and chronic kidney disease rats, to study the adverse effects of excess tryptophan. Design: In Part I Experiment, the healthy rats were fed with diet containing 0.6%, 1.2% and 1.8% tryptophan for 12 weeks. After the intervention, the blood and kidney tissues were collected. Serum creatinine and blood urea nitrogen were detected. Hematoxylin-eosin (H&E) staining was used to observe renal pathological changes. Enzyme-linked immunosorbent assay was used to detect serum kynurenic acid and AhR levels. The kidney levels of AhR, CyP1A1 and CyP1B1 were detected by western-blot. In Part II Experiment, the chronic kidney disease (CKD) model was induced by intra-gastric gavage with adenine for 4 weeks. Then the CKD rats were given tryptophan at a dose of 100mg/kg or 500mg/kg for eight weeks. Rat survival curve, renal function, renal tissue pathology and serum AhR were detected. Tryptophan-targeted ultra-high-performance liquid chromatography coupled with multiple reaction monitoring mass spectrometry (UHPLC-MRM-MS) was employed to quantitatively access the tryptophan-targeted metabolites in two parts experiments. Results: In part I experiment, high tryptophan diet can increase the level of blood urea nitrogen (BUN) in healthy rats and induce focal renal tubulointerstitial injury. Tryptophan-targeted analyses showed that high tryptophan diet feeding can significantly increase the concentration of kynurenine and indole metabolites. The serum AhR level and kidney AhR, CyP1A1 and CyP1B1 were also significantly increased in high tryptophan diet rats. In part II experiment, high tryptophan intervention induced a significant increase in mortality, serum creatinine, urea nitrogen levels, and renal pathological damage in CKD rats. The levels of tryptophan-targeted metabolites, kynurenine, xanthurenate, picolinic acid, 5-hydroxyindole-3-acetic acid, indole-3-lactic acid, indoleacetate and indoxyl sulfate, showed an upward trend in the high-dose tryptophan group (Ade+Trp-H) compared with the adenine group. The serum AhR of Ade+Trp-H rats was significantly higher than those of adenine rats. Conclusion: Moderate tryptophan intake may be beneficial, but excessive tryptophan can lead to accumulation of kynurenine and indole metabolites, activate AhR pathway and induce kidney injury.